A novel antimicrobial peptide screened by a Bacillus subtilis expression system, derived from Larimichthys crocea Ferritin H, exerting bactericidal and parasiticidal activities - Chen, Meiling; Lin, Nengfeng; Liu, Xiande; Tang, Xin; Wang, Zhiyong; Zhang, Dongling (Frontiers in Immunology, 2023)
Antimicrobial peptides (AMPs) may be the most promising substitute for antibiotics due to their effective antimicrobial activities and multiple function mechanisms against pathogenic microorganism. In this study, a novel AMP containing 51 amino acids, named Lc1687, was screened from large yellow croaker (Larimichthys crocea) via a B. subtilis system. Bioinformatics and circular dichroism (CD) analyses showed that Lc1687 is a novel anionic amphiphilic α-helical peptide, which was derived from C-terminal of Ferritin heavy subunit. The recombinant Lc1687 (named as rLc1687) purified from Escherichia coli exhibited strong activities against Gram-positive (Gram+) bacterium Staphylococcus aureus, Gram-negative (Gram-) bacteria Vibrio vulnificus and V. parahaemolyticus, as well as Scuticociliatida. Scanning electron microscope (SEM) and transmission electron microscopy (TEM) revealed the possible function mechanisms of this peptide, which is to target and disrupt the bacterial cell membranes, including pore forming, loss of fimbriae, and cytoplasm overflow, whereas gel retardation assay revealed that peptide Lc1687 cannot bind bacterial DNA. The peptide stability analysis showed that rLc1687 acts as a stable antimicrobial agent against Gram+ and Gram- bacteria at temperature ranging from 25 to 100 ℃, pH 3-12, and UV radiation time ranging from 15 to 60 min. Hemolytic activity assay confirmed that this peptide may serve as a potential source for clinical medicine development. Taken together, Lc1687 is a novel AMP as it is a firstly confirmed Ferritin fragment with antimicrobial activity. And it is a promising agent for the development of peptide-based antibacterial and anti-parasitic therapy.